Experimental characterization of monotonic and cyclic behavior of steel-to-CLT nailed joints strengthened with composite plies. (30th September 2020) - Bellini, Alessandro; Benedetti, Luca; Pozza, Luca; Mazzotti, Claudio
Highlights: Development of an innovative steel-to-CLT strengthened nailed connection. Use of FRP composites for realizing lightweight and hyper-resistant connections. Experimental study of monotonic and cyclic behavior of steel-to-CLT nailed joints. Quantitative evaluation of the reinforcement effect by means of linearization methods. Proposal of a design-oriented analytical capacity method based on adjusted density values. Abstract: Connections play a key role in timber structures because they are the parts devoted to energy dissipation during an earthquake or, when specific hysteretic devices are introduced, their hyper-resistant design allows for a rigid fastening of those devices, thus assuring an elastic behavior of the structure under seismic loads. A promising technique to improve both the load-bearing capacity and the stiffness of joints with dowel-type fasteners, consists in increasing the embedment strength of the wood-based materials, usually by applying a superficial reinforcing layer to the timber-connection shear plane interface. In this framework, results of an experimental campaign carried out on steel-to-CLT panel nailed joints strengthened with a carbon fiber ply glued to the shear plane interface are presented and discussed in this paper. Two different load configurations (perpendicular and parallel to grain) and two different loading protocols (monotonic and cyclic) have been considered, analyzing the results in order to evaluate the effectiveness of the reinforcement technique in terms of load-bearing capacity and stiffness, with respect to the reference unreinforced configuration. Finally, the applicability of the current design method is verified together with the proposal of a simplified design procedure.